Study of the consumption of reducing sugars during the alcoholic fermentation of the grape must Italy to obtain white wine - Robles Calderón, Roberto (2016)
This research aims to determine the time of anaerobic fermentation by reducing sugar intake, inoculating the wort with 4 g/L of Saccharomyces Cerevisiae yeast strains (Lalvin D 47), keeping the fermentation to the following conditions: Acidity 6.5 g/L, temperature 16 °C and Ammonium phosphate 0,2 g/L (nutrient). It was used as raw material grape Italy, from the Province of Cañete. The initial conditions must have been: Brix, 22; acid, 5.7 g / L. The fermentation process was performed in a glass container of 10 L, to which a gas trap adapted to output the CO2 formed during fermentation. To maintain the fermentation temperature, cooling equipment was used. The fermentation time to the above conditions has been 21 days, yielding a wine with residual sugar 1%, aromatic and of good quality.